2017
DOI: 10.1080/16549716.2017.1290340
|View full text |Cite
|
Sign up to set email alerts
|

Childhood pneumonia diagnostics: community health workers’ and national stakeholders’ differing perspectives of new and existing aids

Abstract: Background: Pneumonia heavily contributes to global under-five mortality. Many countries use community case management to detect and treat childhood pneumonia. Community health workers (CHWs) have limited tools to help them assess signs of pneumonia. New respiratory rate (RR) counting devices and pulse oximeters are being considered for this purpose.Objective: To explore perspectives of CHWs and national stakeholders regarding the potential usability and scalability of seven devices to aid community assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…In order to better understand current barriers to the use of pulse oximetry by healthcare providers (HCPs) in a range of healthcare settings and explore opportunities that this technology provides, input from end-users is needed. 20 With the ultimate goal of designing a universal paediatric probe for all levels of healthcare services in resource-poor settings, we aimed to gain an understanding of the challenges of pulse oximetry, how its use has changed service provision and how current devices could be improved for these settings. This end-user perspective is currently limited in the literature and is essential to ensure investment in pulse oximetry is sustainable and effective.…”
Section: Introductionmentioning
confidence: 99%
“…In order to better understand current barriers to the use of pulse oximetry by healthcare providers (HCPs) in a range of healthcare settings and explore opportunities that this technology provides, input from end-users is needed. 20 With the ultimate goal of designing a universal paediatric probe for all levels of healthcare services in resource-poor settings, we aimed to gain an understanding of the challenges of pulse oximetry, how its use has changed service provision and how current devices could be improved for these settings. This end-user perspective is currently limited in the literature and is essential to ensure investment in pulse oximetry is sustainable and effective.…”
Section: Introductionmentioning
confidence: 99%
“…A number of activities were conducted before the field trials to select the test devices. First, the formative research was conducted to inform the attributes used in the subsequent device scoring [ 20 ]. Second, an initial landscape review was conducted where 188 possible devices were identified [ 21 ]; these devices were further evaluated in a review of technical specifications [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Both, health and project field staff were trained, monitored and supervised monthly in the use of PPOs to assess ARI cases equally. PPOs have been underutilised in resource-limited health care settings for a variety of reasons, including high cost, inadequate supply and lack of training [55]. Our design overcomes these limitations and furthers the research on the usefulness and effectiveness of PPOs for ARI case assessments.…”
Section: Discussionmentioning
confidence: 99%